The effects of tranexamic acid on the histopathology of defect healing in an in vivo porcine model after gastric and colonic endoscopic submucosal dissection - Bermont, Anton; Matalon, Shay; Cohen, Daniel L.; Richter, Vered; Siman-Tov, Yariv; Shirin, Haim; Vosko, Sergei (Frontiers in Medicine, 2024)
Introduction: There is limited data on the histopathological effects of hemostatic agents (HAs) used during endoscopic submucosal dissection (ESD). We used an in vivo porcine model to compare the tissue effects of tranexamic acid (TXA) and adrenaline (epinephrine) compared to controls. Methods: Standard ESD, using a 2 mm flash-knife, was performed in three pigs. Four resections were performed in the stomach and rectum of each pig. Injectate contained 4% succinylated gelatin solution and indigo carmine, plus either TXA, adrenaline, or neither. Pigs were euthanized after 7 days and evaluated by two blinded pathologists. Results: Twenty-four defects were analyzed. Within each animal no significant histopathological changes were noted between the defects, but differences were noted between the animals. In the stomachs of the TXA and adrenaline pigs, pathology revealed a clear ulcer in the mucosa/submucosa with abundant granulation tissue, while the muscular layer was unaffected. In the control pig's stomach, the lesions were deeper, transmurally distributed, with inflammation of the muscular and adventitia layers accompanied by severe inflammation and necrosis. Fewer differences were noted in the rectum. Conclusions: For ESD, HAs such as TXA and adrenaline may have protective effects on the depth and extent of injury to the underlying tissue.